Solve for x: 16^2 + (7 - x)^2 = 22- (2x/5)^2

1 Answer | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

The equation you gave is : 16^2 + (7=x)^2 = (22- (2x/5)^2

I think it should be 16^2 + (7 - x)^2 = 22 - (2x/5)^2, the appropriate changes have been made.

16^2 + (7 - x)^2 = 22 - (2x/5)^2

=> 16^2 + 49 + x^2 - 14x = 22 - 4x^2 / 25

=> (305 + x^2 - 14x)* 25 = 22*25 - 4x^2

=> 305*25 + 25x^2 - 350x = 550 - 4x^2

=> 7625 + 25x^2 - 350x = 550 - 4x^2

=> 29x^2 - 350x + 7075 = 0

x1 = [-b + sqrt (b^2 - 4ac)] / 2a

=> x1 = [ 350 + sqrt ( 350^2 - 820700)]/58

=> x1 = [ 350 + sqrt ( -698200)]/58

=> x1 = 350 / 58 + i* (10/58)*sqrt 6982

x2 = 350 / 58 - i* (10/58)*sqrt 6982

The required solution of x is 350 / 58 + i* (10/58)*sqrt 6982 and 350 / 58 - i* (10/58)*sqrt 6982

We’ve answered 318,992 questions. We can answer yours, too.

Ask a question